The Model of the Development of Instructional Material for Enhancing Students’ English Speaking Skills at Elementary Schools in Bandar Lampung - Akhmad Sutiyono (International Conference on Education and Language (ICEL), 2014)
The main problem of the research is what instructional material that should be developed to enhance students’ speaking skills. The main objective of this research is to develop English instructional material for enhancing students’ speaking skills at elementary schools. In conducting the research, the writer used Research and Development method. The data of the research were collected through observation, questionnaire, interview, test, and documentation. The validation of the model was carried out through quasi experiment with pretest-posttest control group design. To compare the students’ speaking skill of pretest and posttest of the experimental class and the students’ speaking skill of the experimental class and the control class, the writer used t-test. The research finding shows that the instructional material developed is effective for enhancing students’ speaking skills. The average scores of pretest of the experimental class and the control class are nearly the same; it means that the students’ speaking skills of the experimental class and the control class is not different significantly. However, the average score of posttest of the experimental class is higher than the control class. Therefore, the writer draws conclusion that the model of instructional material developed is able to enhance students’ speaking skills.